(3QSGdI aj GdYde GdWHjYi hGdEdgis - (3bQIHGTjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO ajbhd eMeO Hf YHO Gddg GdUOjbi GdeOYh dg HMajO Ydi GdfKGQi EYde Cf ai eWdb GdYde KdGKI ePGgH GdChd JUhQ eGgjI GdYde s
(3BNQgG (B:s
(3EYde Cf GdeWGdH Edi jWdH HGdOdGFd KdGKI CbSGe GdChd eGdGjecf EKHGJg EdG HGdfbd dchfg ZGFHkG Yf GdYbd EP jeJfY NdGag YbdkG HGdOdjd GdYbdi GdOGd Ydjg JeJ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3GdadSaI hGdefWbs